Analisis Determinan Konsentrasi Spasial Industri Manufaktur Menengah Besar Indonesia: Studi Kasus Pulau Jawa 2008-2018 - Selly Novia (Universitas Diponegoro, 2023)
This study aims to explain the spatial concentration and the factors that influence the spatial concentration of medium and large manufacturing industries in Java. In the period 2008 to 2018 the manufacturing industry sector contributed about 22% of Indonesia's GDP. This is evidence that the manufacturing industry is the leading sector and the main key in growing the national economy. Java Island is designated as a national growth center by the Master Plan for the Acceleration and Expansion of Indonesian Economic Development (MP3I) where Java Island is a driving force for national industry and services because of the great potential possessed by each province on the island. Analysis of industrial spatial concentration conditions was carried out using the Ellison-Glaeser Index and LQ. The data used is data on the number of large and medium industrial workers according to the two-digit code KBLI 2005 and 2009 at the provincial level on Java Island from 2008 to 2018. The results of the analysis show that the condition of large and medium industries is most concentrated in the tobacco processing industry and scattered industries, namely the rubber industry and plastic products. Analysis of the factors that affect spatial concentration in Java is done by analyzing panel data. The data used is secondary data sourced from the Badan Pusat Statistik (BPS), with cross-sectional data consisting of 6 provinces in Java and time-series data from 2008-2018. The analytical tool used in estimating the regression model in this study is Ordinary Least Square (OLS). The results of this study found that the labor productivity variable had a positive effect on spatial concentration. Meanwhile, the competition index and the provincial minimum wage have a negative effect on the spatial concentration of large and medium manufacturing industries in Java.